2005
DOI: 10.1007/s10725-004-6443-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and biomass production in potato grown in the hot tropics as influenced by paclobutrazol

Abstract: Two similar field trials were carried out during 2003 in a hot tropical region of eastern Ethiopia to investigate the effect of leaf and soil applied paclobutrazol on the growth, dry matter production and assimilate partitioning in potato. A month after planting paclobutrazol was applied as a foliar spray or soil drench at rates of 0, 2, 3, and 4 kg a.i. paclobutrazol ha À1 . Plants were sampled during treatment application and subsequently 2, 4, 6 and 8 weeks after treatment application. The data was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 35 publications
(40 reference statements)
6
44
0
5
Order By: Relevance
“…There are contradictory statements regarding paclobutrazol, if it favors tuber Tekalign et al (2005) mention that may cause decreased performance, Flores et al (2011) confirmed to mention that some of the concentrations studied from 200 to 250 mg L -1 decrease biomass tubercle, while at concentrations of 150 mg L -1 no significant difference with the control without paclobutrazol in this sense.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are contradictory statements regarding paclobutrazol, if it favors tuber Tekalign et al (2005) mention that may cause decreased performance, Flores et al (2011) confirmed to mention that some of the concentrations studied from 200 to 250 mg L -1 decrease biomass tubercle, while at concentrations of 150 mg L -1 no significant difference with the control without paclobutrazol in this sense.…”
Section: Resultsmentioning
confidence: 99%
“…Existen afirmaciones contradictorias en relación respecto al Paclobutrazol, si favorece la tuberización, Tekalign et al (2005), mencionan que puede provocar disminución de rendimiento, Flores et al (2011) lo confirman al mencionar que algunas de las concentraciones en estudio de 200 a 250 mg L -1 disminuyen la biomasa de tubérculo, mientras que a concentraciones de 150 mg L -1 no hay diferencia significativa con el testigo sin Paclobutrazol en este sentido.…”
Section: Resultsunclassified
See 3 more Smart Citations